Genetic characterization of chickpea genotypes using principal component analysis in diallel mating design - Jainendra Pratap,; Shiva Nath,; Anupam Tripathi, (The Bioscan, 2025)
Experimental material consisted of 10 parents and 45 crosses, these crosses were developed by using half diallel mating design. 55 genotypes were evaluated in randomized block design with three replications. Crop geometry consisted of four rows per plot, each measuring 4 meters in length, with a 30 x 10 cm gap between each row and plant. Only three of the nine PCs had an Eigen value greater than 1.0 and a variability of 73.56%. While PC2 accounted 20.38% of the total variation and was strongly correlated with plant height, days to 50% flowering, number of primary branches per plant, and seed yield, PC1 contributed 38.83% of the total variation and was positively correlated with days to flowering and days to maturity. Primary branches per plant, secondary branches/plant, pod/plant, harvest index, seed output, days to 50% flowering, and days to maturity are all related to PC3, which accounted for an extra 14.33% of the overall variation. Using a hierarchical clustering technique, 55 genotypes were divided into 6 clusters. For the majority of the parameters examined, the current study showed that the chickpea germplasm exhibited significant genetic variation.